Optimization of oil palm protoplast isolation and transformation method for transient expression assays using DsRED reporter gene - Md Piji, Mohd Al Akmarul Fizree (2021)
Genetic engineering is highly regarded as a forefront technology in agriculture. Various crops have been improved via this technology to increase the overall yield or specific product of targeted crops. Genetic engineering has also been carried out to address multiple issues that cause production losses, including drought conditions or susceptibility to pest and pathogen attacks. The steady progress and maturation of genome editing technology have allowed scientists to do this more precisely and efficiently. Nevertheless, multiple tools for the target crop, such as an established transformation method for optimal DNA delivery, a reliable transient expression system for preliminary evaluation of the targeting efficiency, and a proven tissue culture routine for regenerating genome-edited plantlets, are required. This current research was carried out to develop a high-throughput transient expression system for oil palm by utilizing protoplasts isolated from oil palm in vitro-derived leaves. First, seven transformation vectors that carry DsRED protein-encoding genes, each controlled by a different promoter, were constructed. Next, the isolation of mesophyll protoplasts was optimized by identifying the best parameters affecting protoplast yield and viability, such as enzyme combinations and procedures to obtain clean and viable protoplasts. By doing this, an efficient protocol for isolation of oil palm mesophyll protoplast that can produce up to 2.5 x 106 protoplasts/g FW with up to 94.78% viability was developed. Then, optimization for isolation of protoplasts from the mesocarp of the age around 12 weeks after anthesis (WAA) was carried out with previously optimized enzyme mixtures. After two hours of incubation time, 3.98 × 106 protoplasts/g FW with 85% viability were recovered. Five parameters affecting the polyethylene glycol (PEG)-mediated transformation efficiency were optimized, including DNA and polyethylene glycol (PEG) incubation time, concentrations of DNA and PEG, and duration of heat-shock applied. This study has shown an increment in transformation efficiency of almost 56%. The developed transient expression system was tested with eight DNA constructs with DsRED as a visual reporter gene. This experiment indicated that the CaMV35S promoter drove significantly higher expression of DsRED in oil palm protoplasts than other plants constitutive, oil palm constitutive and tissuespecific promoter tested in this study. This advanced method will serve as a high-throughput transient expression platform in the current pipeline for oil palm genome editing.